The line direction factor in the watercolor text (the rhythm of exaggeration and directness) - Sekran, Prof.PhD Haider Barzan; Moften, Ass.Lecture Riad Majed (Thi Qar Arts Journal, 2022)
The absolute supremacy of water in the texts of modern Iraqi poets called them to take updated rhythmic factors, through which they practiced the poetic text, and took from these factors as a means in writing the updated version of it; According to the theme of the theme bearing themes, and in a way that ensures its adoption as a readable text, it frames its history with a mechanical icon of awareness that the poet imposes on all aspects, as it is linked to the idea of the text and the nature of his era, especially when we are facing the temptation of rhythmic choices, with the poet’s suggestions and loud protests. We also discussed in this research the factor of the line direction as it is a means of carrying the content and the rhythm of its singular approach, and its relationship to the visual element that the poet must have a special mechanism. We found that most of the poets who dealt with the text of water varied in the contents of the rhythm of their texts and took it as an important means of entering into the themes of water and framing it aesthetically.